2020
DOI: 10.24875/acme.m19000064
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of thrombotic events and complications associated to inferior vena cava filters in patients with and without anticoagulation therapy

Abstract: Incidencia de eventos trombóticos y complicaciones asociadas al uso de filtros de vena cava en pacientes en pacientes con o sin terapia anticoagulante

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…38,39 Early retrieval within 30 to 60 days of postplacement, as supported by others, 14 is an optimal strategy. An interesting observation, which was recently corroborated by others, 40 was that AC did not impact the rate of complications, suggesting that AC is not protective against thrombosis in patients with indwelling VCFs and retrieval should be prioritized.…”
Section: Discussionmentioning
confidence: 54%
“…38,39 Early retrieval within 30 to 60 days of postplacement, as supported by others, 14 is an optimal strategy. An interesting observation, which was recently corroborated by others, 40 was that AC did not impact the rate of complications, suggesting that AC is not protective against thrombosis in patients with indwelling VCFs and retrieval should be prioritized.…”
Section: Discussionmentioning
confidence: 54%
“…[21][22][23] In our study, we observed a filter thrombus incidence of 10.1% in all patients receiving anticoagulation therapy, which may have accounted for this. In contrast, some studies 24,25 have shown that patients with IVCF on anticoagulation have equivalent rates of thrombotic events compared to patients without anticoagulation. Therefore, whether anticoagulants could significantly decrease the incidence of filter thrombi remains elusive.…”
Section: Discussionmentioning
confidence: 93%
“…However, other studies have suggested that thrombosis in the filter is independent of anticoagulation. 32 We believe that thrombosis in IVCFs is associated with inadequate anticoagulation, thrombosis progression, and thrombus shedding in the acute phase of DVT. Most importantly, if we hypothesize that the thrombus in IVCFs has occurred from shedding in the acute phase of DVT, these patients might develop PE.…”
Section: Discussionmentioning
confidence: 96%